Analysis of Public Satisfaction in Tlocor Marine Tourism - Sukmana, Hendra; Rodiyah, Isnaini; Rustianingsih, Eni (Universitas Muhammadiyah Sidoarjo, 2024)
The facilities and infrastructure of a tourist attraction are an important factor in assessing public satisfaction in the tourism sector. This is useful in providing comfort for tourists to visit it. The problem with Tlocor Marine Tourism is the lack of internet connection and the hot tourist atmosphere. Apart from that, to board the ship, visitors must wait until there are a minimum of 10 people before they can depart for their destination. This research aims to analyze the level of satisfaction of visitors and the public at Tlocor Marine Tourism. The method used is a quantitative descriptive approach with a research sample of 60 people consisting of 30 visitors and 30 people from the community around Tlocor Marine Tourism. The data analysis technique used is the crosstab model, which compares visitor satisfaction with the satisfaction of the community around Tlocor Marine Tourism. The research results show that the level of visitor satisfaction at Tlocor Marine Tourism is 46 percent in the high category. Meanwhile, the level of satisfaction of the surrounding community at Tlocor Marine Tourism is 50 percent in the very high category.